Towards anarchy? - Huhnen, Mark (Murmurations: Journal of Transformative Systemic Practice, 2023)
The theme of this edition on decolonisation inspired me to remember, rethink and reclaim my relationship with a philosophical and political idea and movement: anarchy and anarchism. Despite having tried to distance myself from this label in the past due to its negative connotations, I now move towards it and embrace it. Finding connections in my own history, I roughly outline anarchism’s history and some of the diversity of the ideas labelled as anarchist. I will explore how these ideas, particularly the concepts of ontological and political anarchism and the idea of assemblages of power, directly influence my therapy and leadership coaching practice. I believe that some ideas within anarchism align well with systemic theory and can be an inspiring companion in our processes of decolonising our practice.